Poly(lauryl methacrylate-co-1, 6-hexanediol ethoxylate diacrylate) modified silica-based dispersive solid-phase extraction for determination of phenylurea herbicides in environmental water samples. Issue 9 (15th July 2018) - Kuo, Ping-Hui; Lin, Shu-Ling; Fuh, Ming-Ren
ABSTRACT: In this study, poly(lauryl methacrylate- co -1, 6-hexanediol ethoxylate diacrylate) (LMA-HEDA) was synthesised on silanised silica through free-radical cross-linking polymerisation process. The optimal preparation process was obtained by investigating the effects of polymerisation temperature and reaction time. Characterisation of the LMA-HEDA-modified silica was achieved using diffuse reflectance FT-IR. The resulting LMA-HEDA-modified silica was then utilised as a sorbent for dispersive solid-phase extraction (dSPE) of phenylurea herbicides (PUHs) from various environmental water samples. The optimisation of LMA-HEDA-based dSPE process was achieved by investigating the effect of the following parameters including extraction time, pH of sample solution, composition of elution solvent and addition of salt on the extraction recovery of PUHs from water samples. Gradient elution was performed to analyse the extracted PUHs by high performance liquid chromatography (HPLC) with UV-photodiode array detection. Acceptable matrix effect was observed using the proposed LMA-HEDA-based dSPE-HPLC-UV for determining PUHs in environmental water samples. Relatively low detection limits (0.027–0.053 ng mL −1 ) and good linearity (0.1–4.0 ng mL −1 ; r 2  > 0.999) for individual PUHs were obtained using the proposed method. The proposed method offered detection limits lower than the allowed permissible level (0.1 ng mL −1 ) set by European Union. The enrichment factors of target PUHs were also estimated at 40.3–47.7. Good extraction recoveries (80.1–97.9%) for PUHs-spiked water samples were obtained with relative standard deviations lower than 8.7%. The intra-day/inter-day precision (0.7–4.6%/0.2–5.9%) and accuracy (96.7–104.2%/95.3–103.6%) of the proposed method were also evaluated in this study. In addition, the applicability of the developed method was demonstrated by the measurement of PUHs in various environmental water samples.